The Common Christian Responsibility Toward Areas of Rapid Social Change (The ecumenical review, 1955)
This document which bears the sub-title “A Study of the Meaning of Responsible Emancipation” describes the main study project of the Department on Church and Society and was presented by the committee of that Department to the Central Committee of the World Council of Churches